PERANAN ORGANISASI NELAYAN DALAM WADAH HIMPUNAN NELAYAN SELURUH INDONESIA (HNSI) CABANG CILACAP TERHADAP PENINGKATAN KESEJAHTERAAN NELAYAN DI KABUPATEN CILACAP - Kristian Cahyandi; Indriyani; Altril Rayendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2018)
HNSI can encourage the creation of transformations, both in the social, economic and cultural fields so that fishermen are more advanced, independent, and able to achieve sustainable prosperity. HNSI Cilacap in particular can facilitate strengthening the role of fishermen to participate in development processes. As a fisherman organization, HNSI should be committed that it is time for fishing communities to be increasingly given a growing impetus in sea governing. It is therefore the most important agenda for HNSI to continue to encourage local governments to provide adequate facility space (appropriate technology and affordable market access), enhancement of fisherman's human resources, and legal alignment to enable fishermen to become empowered professions.